Littoral cell angioma of the spleen - Coico-León, Amparo Y. (2020)
A 62-year-old man with a medical history of a painful abdominal mass in left upper quadrant and general symptoms, who was classified initially as an unresectable sarcoma. He received chemotherapy and radiotherapy with no response, so he underwent a new surgery, finding a heterogeneous tumor with immunohistochemical consistent with littoral cell angioma. Littoral cell angioma (LCA) is a rare splenic lesion that presents general symptoms, so there are not many reports, which requires surgical management. Is usually an asymptomatic neoplasm of incidental finding, affecting both sexes equally, whose diagnosis is histological and immunohistochemical with a good prognosis always after a surgical approach.